Analisis Kemampuan Dosen Mata Kuliah Rumpun Kependidikan dalam Menyusun RPS Berbasis Outcome Based Education - Fery Darmawan; Bintang Arif Samudra; Nur Haliza Palem; Siti Halimah (Lembaga Yasin AlSys, 2026)
The implementation of an Outcome-Based Education (OBE) curriculum has become a global quality standard in higher education to ensure the measurability of graduate competencies, making lecturers’ ability to design OBE-based Rencana Pembelajaran Semester (RPS; Semester Learning Plans) crucial for academic accountability. This study aimed to analyse the ability of lecturers teaching courses in the education cluster to develop OBE-based RPS. Using a qualitative approach and content analysis method, the study examined RPS documents prepared by permanent lecturers at Universitas Islam Negeri Sumatera Utara selected through purposive sampling. The research instrument was an RPS evaluation rubric encompassing aspects of learning outcomes, learning strategies, and authentic assessment systems. The findings showed that, collectively, lecturers’ abilities were in the “good” category, with an average score of 3.9. The results also revealed constructive alignment between Programme Learning Outcomes (CPL), Course Learning Outcomes (CPMK), and active, Student-Centered Learning-based instructional methods. Nevertheless, weaknesses remained at the level of technical operationalisation, particularly the absence of explicitly stated Sub-CPMK labels and the low quality of measurable performance indicators (measurable outcomes). The implications of this study underscore the need to strengthen lecturers’ capacity in designing more precise assessment matrices to support academic accountability in Lembaga Pendidikan Tenaga Kependidikan (LPTK) and the sustainable implementation of OBE-based curricula.